Appraising and Reacting to Perceived Pay For Performance: Leader Competence and Warmth as Critical Contingencies - Kong, Dejun Tony; Park, Sanghee; Peng, Jian (Academy of Management Journal, 2023)
While pay for performance (PFP) is widely adopted in organizations to boost employee performance, the empirical evidence on its incentive effect has been mixed. Based on Park and Sturman’s (2021) PFP perception framework, we integrated two motivation theories—transactional theory of stress and role engagement theory—to delineate two countervailing mechanisms that explain how individuals appraise and react to perceived PFP. Our study considers employees’ perception of PFP-I (perceived PFP based on individual performance) and highlights leader competence and warmth as critical contingencies. We propose that perceived PFP-I is appraised by employees as a challenge when leader competence is high, which leads to employees’ work engagement and enhanced task performance, but is appraised as a threat when leader warmth is low, which leads to employees’ work withdrawal and decreased task performance. In two three-wave survey studies, we found support for our model. The present research advances our knowledge regarding the incentive effect of PFP-I by emphasizing the importance of perceived PFP-I and proposing a new way of seeing employee motivation and performance ensuing from perceived PFP-I through the lens of stress and role (dis)engagement. Our findings provide insights into how organizations and leaders can effectively utilize PFP to motivate employees.